La “fabrique” de la démocratisation scolaire : indicateurs statistiques et “consignes” d’évaluation - Sandrine Garcia (Cahiers de la Recherche sur l'Education et les Savoirs)
This article attempts to show that the thesis of school democratisation is conditioned by the choice of criterions accepted to measure the access to educational system of different social categories. Thus, not taking the existence of different branches in high school and university into account, one may speak of democratisation not only quantitative but also qualitative as L.A. Vallet and C. Thélot suggest it. Nevertheless, because the different branches have unequal curricula and are organised into a strong hierarchy, measuring such a global school achievement as the standard of education brings to a redefinition of democratisation stakes substituting larger access to diploma for knowledge equalisation. This one doesn’t affect the quasi monopoly of favoured social categories on socially and schoolishly valorised branches. On the opposite, it appears as a condition of a compromise between requirement of democratisation and school and social inequalities reproduction.